1999
DOI: 10.1046/j.1523-5378.1999.98290.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Ulcer Formation after the Hanshin‐Awaji Earthquake: A Case Study of Helicobacter pylori Infection and Stress‐Induced Gastric Ulcers

Abstract: H. pylori infection may play an important role in the development of GUs that are induced by emotional life-event stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 23 publications
(58 reference statements)
0
14
0
Order By: Relevance
“…Indeed, H. pylori infection cannot account for the pathogenesis of gastric ulcer by itself, since most infected individuals do not develop ulcers. The great Hanshin earthquake in Kobe, Japan in 1995 was strongly associated with a significant increase in the development of gastric ulcers and their complications in H. pylori-infected patients compared to non-infected individuals [90,91]. The hypothesis seems to be confirmed after the results of experimental work.…”
Section: Stomachmentioning
confidence: 88%
“…Indeed, H. pylori infection cannot account for the pathogenesis of gastric ulcer by itself, since most infected individuals do not develop ulcers. The great Hanshin earthquake in Kobe, Japan in 1995 was strongly associated with a significant increase in the development of gastric ulcers and their complications in H. pylori-infected patients compared to non-infected individuals [90,91]. The hypothesis seems to be confirmed after the results of experimental work.…”
Section: Stomachmentioning
confidence: 88%
“…This indicates that in chronic, relapsing DU disease, the H. pylori infection itself is the egg, and the increased neuroticism and anxiety the chicken. The relation between life-event stress and H. pylori-infection was highlighted in a study of gastric ulcer formation after an earthquake in Japan in 1995 (17). It was found that 83.1% of the patients who developed gastric ulcer after the earthquake were infected with H. pylori, indicating that H. pylori is a potent risk factor enhancing the ulcer development when a person is subject to environmental stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, notwithstanding the importance of H. pylori for peptic ulceration (and gastric cancer), several studies in the human and in rodents show that stress plays a significant role in peptic ulceration (Matsushima et al 1999, Kim et al 2002, Levenstein 2009, McColl 2009). The role of stress in the causation of peptic ulceration in the human is exemplified by the fact that the HanshinAwaji earthquake, which occurred on 17 January 1995, was followed by a significant increase in the number of people with peptic ulceration (McColl 2009, Levenstein et al 2015.…”
Section: Helicobacter Pylorimentioning
confidence: 99%